Insider trading revisited - Martin, Deryl W. (Journal of business ethics, 1991)
A recent article in this Journal argued that insider trading is an unethical practice leading to an inefficiently functioning market. The debate on this topic has primarily pitted ethical defenses of prohibition against economic arguments extolling its allowance. In addition to being incomplete, this approach ignores other unwanted economic effects of prohibition itself and unethical implications of its existence. This article shows that Adam Smith's free market concept, when properly interpreted, provides all the incentive structure necessary for an efficient and ethical marketplace even when insider trading is permitted.